2013
DOI: 10.1007/s00520-013-2076-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, randomized, double-blind, placebo-controlled study of modafinil for fatigue in patients treated with docetaxel-based chemotherapy

Abstract: Assessing and managing chemotherapy-related fatigue remains a major challenge. There was a lack of difference between the two arms in the planned primary endpoint. However, there was a modest but consistent trend towards improvement of docetaxel-related fatigue in those treated with modafinil. Based on the study findings, modafinil for the treatment of fatigue associated with docetaxel chemotherapy elicits modest improvements. Larger, longer term, randomized, controlled studies are required to clarify the exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…This is consistent with other trials that have not demonstrated an effect of armodafinil or modafinil on fatigue in cancer patients [24-26]. Trials in populations other than cancer have reported a significant improvement in daytime fatigue with the use of armodafinil [40-42].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with other trials that have not demonstrated an effect of armodafinil or modafinil on fatigue in cancer patients [24-26]. Trials in populations other than cancer have reported a significant improvement in daytime fatigue with the use of armodafinil [40-42].…”
Section: Discussionsupporting
confidence: 89%
“…In one study, modafinil was shown to elicit modest improvement in chemotherapy-related fatigue in patients with metastatic breast or prostate cancer [24]. By contrast, other studies have shown that modafinil was not significantly different from placebo for reducing fatigue in patients with lung cancer [25] or primary brain tumor [26].…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria included docetaxel dose reduction (to ≤50 mg/m 2 ), a history of chronic fatigue, uncontrolled hypertension, a psychological condition that prevented treatment or follow-up, or a serious concomitant medical illness, precluding safe prescription of modafinil. Other eligibility criteria have been previously described [1]. Prednisolone at the usual dose of 10 mg daily was given as part of the treatment protocol.…”
Section: Samplesmentioning
confidence: 99%
“…Data for this secondary analysis was obtained from patients enrolled in the MOTIF study [1]. The original phase III, multicentre, randomised (2:1), double-blind, placebocontrolled study evaluated the efficacy of modafinil in patients with metastatic prostate or breast cancer undergoing docetaxel chemotherapy (every 3 weeks; minimum dose 50 mg/m 2 ).…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation